Tingkat Kolaborasi Peneliti pada Program Insentif : “Semi Top-Down”Kementrian Riset dan Teknologi, Tahun 2008-2010) - Setiowiji Handoyo; Prakoso Bhairawa Putra (STI Policy and Management Journal, 2012)
Incentive programs the Ministry of Research and Technology (KRT) is a stimulant in order to increase collaborative research in Indonesia. Collaborative research to be a bridge of cooperation between researchers and organizations, both in terms of human resources, equipment, funds, ideas, and so forth, all through the funding support of KRT. In order to reveal the research activities financed from the Incentive Program, the research was conducted. Another objective of this research is to see how the level of collaboration/cooperation on research conducted by the researchers conducting incentive. This research is a descriptive study using quantitative data. Source data from KRT incentive program managers. Analysis was performed on all activities financed incentive incentive program KRT during 2008-2010. The results of this study concluded that from 1226 the activities carried out in the years 2008-2010 incentive program KRT greatest activity conducted applied research on the types of incentives (498 events). Meanwhile, according to the focal plane, most activities are in the areas of food security (386 events) and according to science should be in the field of engineering sciences (553 events). Collaboration of researchers at the activity level incentives earned 20.43% done in collaboration by two or more researchers.